A convex-deformable sandwich panel for mobile devices. (March 2023) - Jeong, Yoon Chang; Park, Eun-Byeol; Kang, Kiju
Panels with monolithic auxetic micro-architectures are capable of bending into convex shapes. However, the thickness of panels with these micro-architectures (such as re-entrant trusses) is currently under a few millimeters; thus, they are too compliant for structural applications. Moreover, their interior spaces are commonly divided into very small cells to accommodate solid parts. Therefore, a novel sandwich panel composed of stainless steel face sheets with a two-dimensional auxetic pattern and a 3D-printed polymer truss core is proposed as a kinematically and statically determinate structure. This structure allows for a three-dimensional convex deformation under buckling and bending loads. The sandwich panel exhibits high structural robustness and can accommodate thick solid parts within the core. Even when packed with irregular solid chips in the core, a square panel with a 100 mm side length and 4 mm thickness can be deformed up to a minimum curvature of 83.3 mm under extreme five-point bending. Thus, this panel is expected to be used as the main structure for mobile devices, designed for convenient carrying in typical jean's back and thigh pockets.